Penegakan Hukum Terhadap Tindak Pidana Prostitusi Online Anak Dibawah Umur (Studi Penelitian Kabupaten Nagan Raya) - Erfita Ramadhani; Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
In the pandemic era, technology is one way to do activities to facilitate a human activity, the legal aspects that regulate life which aims to regulate harmonization between humans are often violated by certain elements to gain profits, apart from globalization, prostitution also participates Entering the realm of online media, there are many pimps who promote prostitution on social media. Violating online postings violate not only moral norms but also legal norms. This social disease occurs in many areas in Indonesia, including Aceh, especially Nagan Raya. This study aims to determine Law Enforcement Against the Crime of Online Prostitution of Minors in Nagan Raya Regency and the obstacles faced in law enforcement against online prostitution crimes. The method in this study is the empirical judicial method by conducting interviews with both informants and respondents who have been determined previously. The results of the study indicate that law enforcement against online prostitution in Nagan Raya Regency has been running and a series of investigations and investigations have been carried out to uncover cases of online prostitution. From the results of the investigation conducted, it is known that the perpetrators of online prostitution crimes for minors use WhatsApp as a transaction medium. For pimps, Article 506 of the Criminal Code (KUHP) states that: "Anyone who takes advantage of the obscene acts of a woman and uses it as a livelihood, is threatened with a maximum imprisonment of one year. The obstacles faced by law enforcement in dealing with online prostitution in Nagan Raya Regency are divided into 2, namely internal and external. Internal obstacles include the lack of legal instruments to ensnare perpetrators (Commercial Sex Workers) and users (consumers) of online prostitution, the lack of police personnel who can immediately follow up on the finding of the cyber team, the need for up-to-date equipment and personnel capabilities to balance the growing cyber crime, the difficulty of completing evidence and witnesses for court filings and the lack of socialization programs related to online prostitution as a preventive measure such as outreach to students. External constraints encountered include the attitude of the people who are permissive and reluctant to report online prostitution that they encounte.